MAKNA PERDAMAIAN DARI SUDUT PANDANG PEREMPUAN GENERASI Z - Gadis Deslinda; Ernawati Ernawati; Intan Wahyu Istiqomah (BUANA GENDER : Jurnal Studi Gender dan Anak, 2021)
This research describes the meaning of peace from the perspective of generation Z women. This generation is also called the millennial generation or today's young people. Z generation women are part of the current generation of young people, who certainly have different perspectives in interpreting peace in this country.There is sufficient evidence regarding the increasing attitude of intolerance among students and today's students.From a number of results of studies of high school students and college students it was revealed that 9.5% of respondents tended to be intolerant of minority groups.From the Campus Islamic Research it was found that 65% of student respondents supported sweeping actions carried out arbitrarily by radical Islamic mass organizations (Directorate General of Higher Education Ministry of National Education, 2007).This fact is interesting to examine further about how generation Z women interpret peace in this country. This research is applied qualitative research and uses the Interpretative Phenomenology Analysis (IPA) approach.The results show four main categories related to the meaning of peace from the perspective of generation Z women, namely making peace with themselves, not easily suspicious and prejudiced with others, respecting differences, and easily forgiving others.Â